Tatak Pilipino [episode no. 69] [videorecording]. ([Quezon City ABS-CBN], 1992)
A unique display of Pilipino ways and style.
Tatak Ethico --Ifugaos and Igorots in Banaue and Sagada -- Burial practices of the Ifugao --Joseph Lamayan, bronze smith -- Pinikpikan -- Hell cutting and headtaking -- Banaue rice terraces -- Jeep services in Banaue -- Bahay Ifugao -- Paintings of Diokno and sine visual of Mosque Ferrer -- Scooters of the Ifugao.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Ferrer, Mosque -- Photograph collections; Ifugaos